Pengaruh Konflik Rumah Tangga terhadap Kesehatan Mental Anak dalam Perspektif Hukum Keluarga Islam: Penelitian - Nurkafidz Nizam Fahmi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Domestic conflict is a dispute or tension that occurs between family members, especially married couples, which can negatively impact family dynamics. The purpose of this study is to obtain a complete, detailed, and systematic description in order to understand the impact, concept or practice, role and responsibility of parents on children's mental health. The method used is qualitative with a normative juridical approach, this study analyzes how parental disputes affect the psychological development of children in Muslim families. The results obtained are that children exposed to domestic conflicts often experience symptoms of anxiety, depression, and behavior disorders. Islam emphasizes the importance of maintaining domestic harmony and protecting the interests of children. Islam has mechanisms to protect children's mental health from the negative effects of domestic conflicts, while still striving for peace and family integrity. The results of this study are expected to provide new insights into efforts to protect the mental health of Muslim children affected by domestic conflicts, as well as enrich the understanding of the implementation of Islamic family law in the modern context.